2016
DOI: 10.4103/0972-3919.178254
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study of 11 C-methionine and 18 F-fluorodeoxyglucose positron emission tomography-computed tomography scans in evaluation of patients with recurrent brain tumors

Abstract: Introduction:11C-methonine ([11C]-MET) positron emission tomography-computed tomography (PET-CT) is a well-established technique for evaluation of tumor for diagnosis and treatment planning in neurooncology. [11C]-MET reflects amino acid transport and has been shown to be more sensitive than magnetic resonance imaging (MRI) in stereotactic biopsy planning. This study compared fluorodeoxyglucose (FDG) PET-CT and MET PET-CT in the detection of various brain tumors.Materials and Methods:Sixty-four subjects of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…In 26.6% (n 5 221) of lesions, follow-up was not specified on the individual lesion level. Several of the included studies analyzed 2 PET tracers per lesion (21,29,(33)(34)(35)41,46,52,53); in total, 951 PET studies (Supplemental Table 5 shows the tracer distribution) were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 26.6% (n 5 221) of lesions, follow-up was not specified on the individual lesion level. Several of the included studies analyzed 2 PET tracers per lesion (21,29,(33)(34)(35)41,46,52,53); in total, 951 PET studies (Supplemental Table 5 shows the tracer distribution) were included.…”
Section: Resultsmentioning
confidence: 99%
“…Fifth, the comparisons between different PET tracers in this review lack statistical support, as this metaanalysis contains largely noncomparative studies of the different PET tracers. Only 2 studies compared 18 F-FDG and 11 C-MET in the same patient population (21,46). We did not directly compare the PET tracers, because the differences in study design, patient groups, and reference standards can confound the differences in diagnostic accuracy (60).…”
Section: Discussionmentioning
confidence: 99%
“…After screening the records for duplications, only 41 of them were potentially eligible for further full text evaluation. In all, 23 articles with a total sample size of 891 patients representing 899 scans that met all inclusion and exclusion criteria were included for the meta-analysis [ 7 9 , 11 30 ]. The PRISMA flow diagram of the study selection process is displayed in Figure 1 , and the basic characteristics of all 23 articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Positron emission tomography (PET) is a promising imaging modality that has been extensively applied in the field of neuro-oncology. The 11C-methionine has been reported to be an excellent tracer for PET imaging, and many prior studies have reported the use of 11C-methionine PET for identifying recurrent tumors [ 7 9 ]. In a previously published meta-analysis [ 10 ], the performance of 11C-methionine PET in distinguishing glioma recurrence was evaluated, but it included few studies and lacked a comprehensive subgroup analysis.…”
Section: Introductionmentioning
confidence: 99%
“…11 C-methionine has been the most widely used amino acid PET tracer. It can differentiate tumours from normal brain with an accuracy of 94% versus 80% for 18 F-FDG [151] and is also more sensitive for differentiating recurrence from radiation necrosis following radiotherapy [152]. However, the application of 11 C-labelled substrates will always be limited by the short half-life (20 min) requiring onsite production of the tracer.…”
Section: Imaging Changes In Metabolismmentioning
confidence: 99%